Affectional interactions with your animated child avatar can enhance wellbeing - Edalat, Abbas; Polydorou, Neophytos; Ryan, Frank; Gilbert, Barnabas J.; Nicholls, Dasha (Frontiers in Virtual Reality, 2024)
The aim of this proof-of-concept study was to evaluate the efficacy of a new virtual reality (VR) platform for practising the Self-Attachment Technique (SAT) in a non-clinical population.The growing prevalence of mental health problems underscores the urgent need for scalable and effective interventions. SAT is a self-administered psychotherapeutic technique where the individual creates an affectional bond with their childhood self and vows to re-raise this child to emotional wellbeing. Digital technologies like VR and avatars can naturally enhance SAT by improving imaginative interactions with the childhood self. Over an 8-week period, participants practised the SAT exercises either by animating their personalised childhood avatar into different emotional states in VR or by imaginatively using their childhood photos.Participants' measurements were collected before and after the intervention as well as at 3-month follow-up, and analysed to understand whether changes over time, in the areas of wellbeing, self-compassion and psychological capital, are significant. Overall, participants experienced significant improvement in wellbeing (primary outcome) with large effect size (r = 0.86). Further exploratory analysis of our findings indicated that the effect of VR (d = 1.12) was better compared to the childhood photos (d = 0.47). Qualitative evidence from the present study suggested that the intervention had a positive impact on participants' daily lives. This study showed that practising SAT using the participant's childhood avatar in a virtual environment has potential for enduring effects that need to be validated in future randomised trials.